PENINGKATAN KESADARAN LINGKUNGAN MELALUI PROGRAM PENANAMAN OBAT DI PUSPA AMAN DESA TEGAL TUGU GIANYAR - Purwaningrat, Putu Atim (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Increasing environmental awareness is an important step in preserving ecosystems and sustainable use of natural resources. This research aims to evaluate the effectiveness of the medicinal plant planting program in increasing environmental awareness in puspa aman, tegal tugu village. The method used includes a qualitative approach with data analysis from interviews, observations and questionnaires conducted with program participants and the local community. The research results show that this program has succeeded in increasing public understanding of the benefits of medicinal plants for health and the environment, as well as encouraging active participation in environmental conservation activities. Program participants reported increased knowledge about local medicinal plants and their impact on health as well as reduced negative impacts on the environment. In addition, there have been positive changes in people's attitudes towards environmental conservation, demonstrated by increased awareness of the importance of maintaining biodiversity and environmentally friendly farming practices. This research concludes that medicinal plant planting programs can be an effective tool in increasing environmental awareness and encouraging broader conservation action in local communities